(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: تهدف هذه الدراسة إلى إبراز خطورة خطاب الكراهية في وسائل الإعلام والاتصال الحديثة، والآثار التي يمكن أن تحدثها في الأفراد والجماعات، خاصة مع التطور التكنولوجي المتسارع في هذا الحقل وظهور منصات رقمية وحسابات افتراضية قلت فيها المسؤولية الاجتماعية وأخلاقيات الممارسة الإعلامية. فنحاول من خلال هذه الدراسة إبراز أهم القوانين والمعاهدات الدولية المناهضة لخطاب الكراهية. لنستقرئ في الأخير قانون 20-05 الجزائري، والمتعلق بالوقاية من التمييز وخطاب الكراهية ومكافحتها. مكافحة جاءت من خلال عدة آليات سنتها الدولة كإشراك المجتمع المدني والقطاع الخاص وإنشاء المرصد الوطني للوقاية من التمييز وخطاب الكراهية غير أننا ركزنا في دراستنا هذه على وسائل الإعلام والاتصال باعتبارها أهم محرك لهذا الخطاب. معتمدين في دراستنا على المنهج الاستقرائي وتحليل الوثائق من معاهدات وقوانين. وقد توصلنا إلى أن القانون 20-05 مميز من حيث آليات االمستحدثة غير أنه يتوجب إرفاقه بقانون إعلام جديد يعزز حرية الرأي والتعبير كحق مكتسب من جهة ويضبط الممارسات تجاه هذا الخطاب من جهة أخرى. كلمات دالة : قانون الإعلام، خطاب الكراهية ، الممارسات الإعلامية Abstract: This study aims to highlight the seriousness of hate speech in the media and communication and the effects it can have on societies, especially with the rapid technological development in this field and the emergence of digital platforms and virtual accounts that do not care and are not responsible for the effects that their speeches can have. Trying to highlight the most important international laws and treaties against this discourse. Finally, let us extrapolate to Law 05-20 related to preventing and combating discrimination and hate speech. Combating this discourse according to the law came through several mechanisms enacted by the state, such as the involvement of civil society and the private sector, and the establishment of the National Observatory for the Prevention of Discrimination and Hate Speech. However, in our study, we focused on the media and communication as the most important driver of this discourse. Relying in our study on the inductive approach and analysis of documents from treaties and laws.We concluded that Law 05-20 is distinguished in terms of the new mechanisms, but it must be attached to a new media law that enhances freedom of opinion and expression as an acquired right on the one hand, and regulates practices towards this discourse on the other hand.Key words: Media Law - Hate Speech - Media Practices